Incidencia de los factores de la satisfacción laboral en los empleados de la empresa Aglomerados S.A - Acosta Vinueza, Karen Liliana (2019)
The purpose of the investigation is to determine how the factors of job satisfaction affect, and if they meet the expectations of workers in the production area of the Company Aglomerados Cotopaxi S.A, which dedicates to the development of chipboard, medium-density fibreboard, and sawn wood. The idea is to show the human value resources have for the organization, and how the company should look for work well-being to achieve the objectives for which it was created to obtain profitability through the satisfaction of the worker. It also demonstrated what are the causes of dissatisfaction at work, and highlight the main ones, as well as find the appropriate ways to solve them. The project worked under the descriptive, qualitative, and non- experimental design approach since the information technology used here was documentary analysis. First, the theoretical aspects of job satisfaction addressed. Second, a scale was used to measure the degree of satisfaction of intrinsic and extrinsic factors, and it concludes with the results that show that workers are somewhat satisfied with their work. Respondents said they have a medium level of job satisfaction (from 44% to 100%) and this is because sometimes they are not recognized for their work performance, suddenly they have interpersonal problems, and some company policies are not to their liking. It is recommended to perform job satisfaction measurements periodically to maintain updated information, and assertive communication proposes as a strategy to improve the satisfaction of human resources, through training